(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2025)
Lung adenocarcinoma (LACA) presents with a range of debilitating symptoms, including chronic cough, hemoptysis, and shortness of breath. In this study, we reanalyzed a published transcriptomic dataset to compare male and female LACA samples with healthy lung tissue and identify potential therapeutic targets capable of reversing disease-associated gene expression signatures. Utilizing cutting-edge bioinformatics approaches, including differential expression analysis, pathway analyses and analyses of signature-reversing drug profiles, we assessed male and female signatures separately. Using Gene Set Enrichment Analysis, we identified sex-specific differences in tumor-associated pathways, including the downregulation of blood angiogenesis in female lung adenocarcinoma subjects. Leading-edge gene analysis further revealed that angiogenesis-related genes were downregulated in both sexes, though the specific genes contributing to these pathways differed between males and females. Integrative drug repurposing analysis using the LINCs database, based on our transcriptomic profiles, uncovered potential therapeutic candidates for male and female LACA compared with healthy controls. Notably, a VEGFR inhibitor showed the highest discordance score in males, while a CLK2 inhibitor demonstrated one of the highest discordance scores in females. Together, these findings highlight distinct molecular and pharmacologic signatures between sexes and suggest potential sex-specific therapeutic strategies for lung adenocarcinoma.